Pineapple root growth and distribution with the use of plastic mulch and percolation barrier - Lima, Lenilson Wisner Ferreira; Coelho, Eugênio Ferreira; Reinhardt, Domingo Haroldo Rudolfo C.; Junghans, Davi Theodoro; Vellame, Lucas de Melo; Barros, Damiana Lima (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the effect of the use of plastic mulch and percolation barrier on the growth and distribution of pineapple roots. The BRS Imperial cultivar was cultivated using plastic as mulching material and a percolation barrier. The evaluated variables were: relative and absolute root growth rates, root length distribution, and root length density. The use of plastic mulch resulted in a greater accumulation of root dry matter, with or without the percolation barrier. Under drip irrigation, mulching promoted a greater root development. The highest root growth rate occurred from 360 to 450 days after planting. The amount of roots was from 64.1 to 66.7% on the stem, and from 34 to 36% distributed in the 0.10 and 0.20 m soil layer. Black plastic, as mulch or a percolation barrier, contributes to increase the root development of 'BRS Imperial' pineapple under drip irrigation.
Keywords: Ananas comosus; mulching; soil cover; water use efficiency